Description and critical reflection of Simone Roach’s caring theory - Luís Condeço; Margarida Vieira; Madalena Cunha (Millenium)
Introduction: Simone Roach conceptualizes caring as the human way of being, emphasizing that caring is not just a professional characteristic, but a fundamental expression of humanity. The applicability of her theory in the context of training nurses or those at the start of their professional careers could prove very useful, due to its focus on the development of patient-centered clinical practice. Its limited use highlights the need for a critical analysis of its contribution to the discipline.